Preventing child abuse: critical roles and multiple perspectives - Palusci, Vincent J.; Vandervort, Frank E.; Greydanus, Donald E.; Merrick, Joav (Pediatrics, child and adolescent health, 2021)
"When we think of child abuse, we imagine several different forms of harmful parenting and injuries to children. Most are not visible to the naked eye, but can be seen if you look more deeply. X-rays can detect fractures and other imaging can find internal injury and bleeding, but most maltreated children have more long-lasting harm that reveals itself through behavioral and emotional maladjustment, developmental delay, sadness, and other destructive behaviors later in childhood, adolescence and into adulthood. These injuries to their personality, sense of self, relationship to society and mental health change the trajectory of their lives and dim their potential, with social and financial costs for safety, treatment and their lost personal growth. We think of these as affecting everybody's children and that the responsibility lies with everyone to respond. This is why we put together this book: to address prevention from a number of perspectives and a variety of professions. We hope that it successfully brings together a number of disciplines and perspectives to address child abuse and neglect among the world's families, governments and cultures. We hope that those reading these chapters will realize that there are replicable best practices that can be reliably implemented based on child and family experiences and needs rather than single approaches designed to attack single forms of maltreatment, and we look forward to the day that books like these are not needed"--